Mechanical properties in relation to vehicle mobility of Sepang peat terrain in Malaysia - Rahman, Mohammed Ataur (Elsevier Ltd., 2004)
An analytical framework for determining the mechanical properties of peat and predicting the tractive performance of tracked vehicle is presented. It takes into account the load-sinkage and shearing characteristics of peat as well as all major design parameters of tracked vehicle. An experimental study on the mechanical properties of peat soil was conducted at Sepang area, Selangor, Malaysia. The stiffness values of surface mat and underlying weak peat deposit from load-sinkage test were determined by specially made bearing capacity apparatus. The mean values of surface mat stiffness before and after drainage were found to be 31 and 45.62 kN/m3, respectively and the mean values of underlying peat stiffness before and after drainage were found to be 252 and 380.20 kN/m3, respectively. The mean value of the internal frictional angle, cohesiveness and shear deformation modulus of the peat soil sample were determined using a direct shear box apparatus in the laboratory. The mean values of internal friction angle, cohesiveness and shear deformation modulus before and after drainage were found to be 22.80° and 24.31°, 2.63 and 2.89 kN/m2, and 1.21 and 1.37 cm, respectively.